2019
DOI: 10.1038/s41368-019-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential Vanilloid 1-based gene therapy alleviates orthodontic pain in rats

Abstract: Orthodontic pain that is induced by tooth movement is an important sequela of orthodontic treatment and has a significant effect on patient quality of life. Studies have shown that the high expression of transient receptor potential vanilloid 1 (TRPV1) in trigeminal ganglions plays a vital role in the transmission and modulation of orofacial pain. However, little is known about the role of TRPV1 in orthodontic pain. In this study, male Sprague–Dawley rats were randomly assigned to six groups to study the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…Indeed, non-steroidal anti-inflammatory drugs (NSAIDs) reduce orthodontic pain in patients and rodents (Bartzela et al, 2009; Shibazaki et al, 2009). Pharmacological inhibition or knockdown of TRPV1 attenuates spontaneous pain behaviors, such as grimace scale or face grooming, induced by orthodontic forces in rats (Gao et al, 2016; Guo et al, 2019a). Our experiments using genetic knockout of TRPV1 further support the contribution of TRPV1 to spontaneous pain behaviors evoked by orthodontic force.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, non-steroidal anti-inflammatory drugs (NSAIDs) reduce orthodontic pain in patients and rodents (Bartzela et al, 2009; Shibazaki et al, 2009). Pharmacological inhibition or knockdown of TRPV1 attenuates spontaneous pain behaviors, such as grimace scale or face grooming, induced by orthodontic forces in rats (Gao et al, 2016; Guo et al, 2019a). Our experiments using genetic knockout of TRPV1 further support the contribution of TRPV1 to spontaneous pain behaviors evoked by orthodontic force.…”
Section: Resultsmentioning
confidence: 99%
“…The role of TRPV1 in non-evoked pain upon the application of orthodontic force was also suggested. Pharmacological inhibition or knockdown of TRPV1 attenuates facial grooming or grimace scale induced by orthodontic force in rats (Gao et al, 2016; Guo et al, 2019a). However, it is not known if TRPV1 contributes to other modalities of orthodontic pain, such as bite-evoked pain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to pharmaceutical approaches, a recent gene therapy study by Guo et al (2019) using a rat model of orthodontic tooth has shown that reduction of TRPV1 expression in the trigeminal ganglia reduces pain induced by tooth movement in the jaw. In this study, lentivirus containing a TRPV1 shRNA gene was injected into the trigeminal ganglia to reduce TRPV1 protein expression and pain levels were assessed using rat grimace scale (RGS) [50]. RGS is regarded as a proxy to score pain levels in the rats which is assessed by looking the signs of pain from the facial expressions and position of the eyes, ears and mouth of the animal.…”
Section: Therapies Targeting Peripheral Nociceptive Circuit Dysfunmentioning
confidence: 99%
“…The integration of viral gene into host genome on one hand is bene cial for stable expression, which makes it a promising gene therapeutic tool for a variety of pain conditions, especially for chronic pain (53)(54)(55). Our previous study revealed that administration of lentivirus containing shRNA aiming at knocking down TRPV1 or ASIC3 was effective in alleviating orofacial pain (56,57). In our present study, transduction of PNOC overexpression lentivirus was successful in overexpressing N/OFQ in trigeminal ganglia and the overexpression was stable on 3 rd day, 5 th day and 7 th day, but not on 14 th day.…”
Section: Discussionmentioning
confidence: 99%